Facile access to a heterocyclic, sp3-rich chemical scaffold via a tandem condensation/intramolecular nitrone–alkene [3+2] cycloaddition strategy - Rawling, M.J.; Storr, T.E.; Bawazir, W.A.; Cully, S.J.; Lewis, W.; Makki, M.S.I.T.; Strutt, I.R.; Jones, G.; Hamza, D.; Stockman, R.A. (Royal Society of Chemistry, 2015)
A heterocyclic, sp3-rich chemical scaffold was synthesised in just 6 steps via a highly regio- and diastereo-selective tandem nitrone formation/intramolecular nitrone–alkene [3+2] cycloaddition reaction. A library of 543 lead-like compounds based on the scaffold core has been produced.